United University Professions pioneering in higher education unionism - Drescher, Nuala McGann (State University of New York Press, 2019)
"Public education, from pre-K through higher education, and labor unions, particularly those representing public sector workers, are today under attack from those who question the very need to have such basic institutions. United University Professions: Pioneering Higher Education Unionism is a history of United University Professions (UUP), which grew from humble beginnings to become the nation's largest higher education union representing some 35,000 academic and professional staff within the State University of New York (SUNY) system. Authors Nuala McGann Drescher, William E. Scheuerman, William Ivan D. Steen chronicle how UUP built upon its early accomplishments at the bargaining table and in the political arena to become a national leader in the struggle to preserve academic freedom and the institution of tenure, the bedrock of academic freedom. More broadly, they argue, UUP in microcosm confirms the importance of unionization not only for the members it represents, but to core American values and American democracy itself"--